2022
DOI: 10.1111/jne.13136
|View full text |Cite
|
Sign up to set email alerts
|

Unusual suspects: Glial cells in fertility regulation and their suspected role in polycystic ovary syndrome

Abstract: Gonadotropin-releasing-hormone (GnRH) neurons sitting within the hypothalamus control the production of gametes and sex steroids by the gonads, therefore ensuring survival of species. As orchestrators of reproductive function, GnRH neurons integrate information from external and internal cues. This occurs through an extensively studied neuronal network known as the "GnRH neuronal network." However, the brain is not simply composed of neurons. Evidence suggests a role for glial cells in controlling GnRH neuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…5a). To identify the source of SEMA6A in the ME, additional staining with markers for different cell types (secretory neurons, astrocytes, β-tanycytes and oligodendrocytes (OLs)) involved in ME homeostasis were performed 43,44 . SEMA6A was not detected in the Synaptophysin + terminals of neurosecretory neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). To identify the source of SEMA6A in the ME, additional staining with markers for different cell types (secretory neurons, astrocytes, β-tanycytes and oligodendrocytes (OLs)) involved in ME homeostasis were performed 43,44 . SEMA6A was not detected in the Synaptophysin + terminals of neurosecretory neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). These cells are known to play key roles in GnRH neuron plasticity 43,44 . Instead, we identified maturing OLs as the source of SEMA6A in the ME (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented herein were obtained using T98G cells, a multiformal human glioblastoma and not in neurons that could secrete GnRH. It should be noted that GnRH neurons do not express the male and female steroid hormone receptors needed for the feedback regulation of the HPGA (Figure 2) [25]. Thus, the action of other cells in HPGA regulation is needed.…”
Section: Regulation Of the Hypothalamic-pituitary-gonadal Axis By Gli...mentioning
confidence: 99%
“…These other cells are glial cells, as we used in our previous experiments [17][18][19]. Indeed, these cells have been suspected of causing infertility disorders, such as polycystic ovary syndrome [25]. It is suggested that glia is able to release soluble factors as transforming factors and neurorregulins, which may affect neurons and other glial cells for regulating the GnRH pathway [26].…”
Section: Regulation Of the Hypothalamic-pituitary-gonadal Axis By Gli...mentioning
confidence: 99%